2015
DOI: 10.4209/aaqr.2015.04.0253
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Particulate Matter and Carbonaceous Aerosol over Two Urban Environments in Northern India

Abstract: Monitoring and simultaneous sampling of Particulate matter (PM 10 and PM 2.5 ) was carried out for the first time over two urban sites in Northern India (Jabalpur and Udaipur) during December 2010-November 2012 (up to August 2012 over Udaipur). The samples of PM 2.5 were analyzed for elemental carbon (EC) and organic carbon (OC) using advanced DRI Thermal optical carbon Analyzer. The monthly mean PM 10 values were as high as 149 ± 44 µg m -3 over Jabalpur (JBL) and 171 ± 42.2 µg m -3 over Udaipur (UDPR). PM 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…This is attributed to the limited outdoor biomass and fossil fuel (coal) combustion activities on account of wet ambient conditions as well as to the removal of particles by rainwater and the process is termed as rain wash out process. Similar observations about low OC and EC in PM 10 of two different sites in India due to wet removal of particles during rainy season have also been made by Panicker et al (2015). The higher OC in autumn season could be linked to the higher plant productivity soon after rainy season and high EC (17.3 µg m -3…”
Section: Oc and Ec Content In Pm 10supporting
confidence: 69%
“…This is attributed to the limited outdoor biomass and fossil fuel (coal) combustion activities on account of wet ambient conditions as well as to the removal of particles by rainwater and the process is termed as rain wash out process. Similar observations about low OC and EC in PM 10 of two different sites in India due to wet removal of particles during rainy season have also been made by Panicker et al (2015). The higher OC in autumn season could be linked to the higher plant productivity soon after rainy season and high EC (17.3 µg m -3…”
Section: Oc and Ec Content In Pm 10supporting
confidence: 69%
“…Average OC/EC ratio was 3.5 at DEL, 5.4 at JHJ and 6.9 at BKR (Table 3). Similar OC/EC ratios have also been reported at other urban sites in India; Patiala (8.7) 41 , Agra (6.7) 49 , Udaipur (6.4) and Jabalpur (4.8) 50 . Burning of wood and cow dung at domestic levels might have resulted in high OC/EC ratio (6.9) at BKR whereas more sources of EC such as vehicular emissions and other combustion processes have resulted in lower OC/EC ratios (3.5) at DEL 30 .…”
Section: Molar Ratios Of Ions and Neutralization Factors (Nf)supporting
confidence: 84%
“…So far studies on fine sized PM (PM 2.5, i.e., PM B 2.5 lm) and coarse sized PM (PM 10, i.e., PM B 10 lm) are reported mainly for urban locations in India (Rengarajan et al 2011;Tiwari et al 2012Tiwari et al , 2013Panicker et al 2015;Pipal and Satsangi 2015;Gawhane et al 2017). Very few studies are reported from high-altitude stations in India (Safai et al 2005;Chatterjee et al 2010;Satsangi et al 2014;Leena et al 2017).…”
Section: Introductionmentioning
confidence: 99%